Biomaterials for Implants and Scaffolds - Li, Qing; Mai, Yiu-Wing (Springer Series in Biomaterials Science and Engineering,, 2017)
This book highlights the latest, cutting-edge advances in implantable biomaterials. It brings together a class of advanced biomaterials in two highly active research areas, namely implants and tissue scaffolds, to underline their respective functional requirements for further development. It is unique in providing a full range of methodological procedures, including materials syntheses, characterisation, cellular tests and mathematical modelling. Covering metallic, ceramic, polymeric and composite materials commonly used in biological applications and clinical therapeutics, it is a valuable resource for anyone wanting to further their understanding of the latest developments in implantable biomaterials. Focusing on biomedical applications in implants and scaffolds, it provides methodological guides to this rapidly growing field. Qing Li and Yiu-Wing Mai are both professors at the University of Sydney, School of Aerospace, Mechanical and Mechatronic Engineering.